Who's Afraid of Terror News? The Interplay between News Consumption Patterns, Personal Experiences and Fear of Terrorism. Issue 3 (4th May 2023) - Jacobs, Laura; van Spanje, Joost
ABSTRACT: A positive correlation between exposure to terrorism news reports and fear of terrorism has been documented, but less is known about factors moderating this relationship. Our focus is mostly on identifying relevant moderators. We argue that individuals' habitual patterns in news consumption (frequency, type of outlet, genre) and personal experiences (prior victimization, living in a diverse neighborhood, residing in an urban area) are relevant in this regard. In a between-subjects experiment (2 groups: exposure to terror threat story vs. control story) in Germany, the Netherlands and Sweden ( N = 786) we exposed participants to a news story on terror threat. Effects on fear of terrorism were especially strong for citizens that often consume soft, popular and commercial forms of news and live in urban areas.